Ab-initio molecular dynamics study of eutectic chloride salt: MgCl2–NaCl–KCl - De Stefanis, Emily; Ramic, Kemal; Vidal, Judith; Zhao, Youyang; Gallington, Leighanne C.; Bedell, Ryan; Liu, Li (Emily) (Frontiers in Nuclear Engineering, 2024)
Ionic liquid materials are viable candidates as a heat transfer fluid (HTF) in a wide-range of applications, notably within concentrated solar power (CSP) technology and molten salt reactors (MSRs). For next generation CSP and MSR technologies striving for higher power generation efficiency, a HTF with wide liquid phase range and energy storage capabilities is crucial. Studies have shown that eutectic chloride salts exhibit thermal stability at high temperatures, high heat storage capacity, and are less expensive than nitrate and carbonate salts. However, the experimental data needed to fully evaluate the potential of eutectic chloride salts as a HTF contender are scarce with large uncertainties. Considering the high cost and potential hazards associated with the experimental methods used to determine properties of ionic liquids, molecular modeling can be used as a viable alternative resource. In this study, the eutectic ternary chloride salt, MgCl2-NaCl-KCl, is modeled using ab-initio molecular dynamics simulations (AIMDs) in the liquid phase. Using the simulated data, thermophysical and transport properties of the eutectic chloride salt can be calculated: density, viscosity, heat capacity, diffusion coefficient, and ionic conductivity. For an initial model validation, experimental pair-distribution function data are obtained from x-ray total scattering techniques and compared to the theoretical pair-distribution function. Additionally, the theoretical viscosity values are compared to experimental viscosity values for a similar system. The results provide a starting foundation for the MgCl2-NaCl-KCl model that can be extended to predict other fundamental properties.